What waits in the water - Scott, Kieran, 1974- (Scholastic, Inc., 2017)
Hannah is excited to spend some time at her best friend Jacob's lake house this summer. The catch? Hannah's annoying new stepsister, Katie, is tagging along. Katie is wild and pretty and seems to have a THING for Jacob. Hannah's not jealous...or is she? To make matters worse, the town they're staying in is sort of...creepy. And as Hannah gets to know some kids in the town, she learns there are all kinds of rumors swirling about the lake. Rumors about mysterious deaths and drownings. And monsters that may lurk below the deep. Hannah doesn't believe any of it...until she sees something horrific happen to a new friend. Did Hannah just witness a murder? Or was this a prank gone awry? And who can Hannah trust now?